Avascular necrosis post unstable slipped capital femoral epiphysis: a treatment algorithm with staged hinged hip distraction: mid-term results. Issue 4 (July 2019) - Balakumar, Balasubramanian; Madan, Sanjeev
Background: Management of avascular necrosis (AVN) of the femoral head in slipped capital femoral epiphysis (SCFE) is difficult. We proposed to ascertain if staged hip distraction could prevent collapse and recover the femoral head. Methods: A retrospective review of the hip database retrieved 16 children with unstable SCFE and AVN. All underwent capital realignment by surgical dislocation followed by 2nd-stage hinged hip distraction. Patient demographics and radiographic parameters of deformity, AVN and arthritis were collected. The patients scored their hip function both before and after intervention and at follow-up using the modified Harris Hip Score and Nonarthritic Hip score. Results: 7 boys and 9 girls formed the study group ( n = 16). The average age at surgery was 12.7 years (9–16 years). 8 rights hips and 8 left hips were involved. The average follow-up was 45 months (33–66 months). Group A ( n = 7) had hip distraction only if the follow-up radiographs showed AVN changes and collapse. Based on the observations in Group A, the protocol was changed for Group B. Group B ( n = 9) underwent hip distraction at 6 weeks of capital realignment for avascularity of the femoral head. In Group A, all patients had further collapse and advanced arthritis at follow-up. In Group B all patients had hip joint space restored and good hip function without pain at follow-up. Conclusions: Pre-emptive application of hip distractor for those children with proven lack of blood flow to the femoral head is a potential option to stall the progression of AVN and to help recover useful hip function.